Pigmentierte villonoduläre Synovialitis des Hüftgelenks bei einer Patientin mit sehr geringer Beeinträchtigung trotz großer radiologischer Auffälligkeiten - van der Plaat, L. W.; Westerga, J.; Staal, K.; Pöll, R. G. (Aktuelle Rheumatologie, 2013)
We report a case of pigmented villonodular synovitis (PVNS) of the hip joint in a patient with very limited impairment despite impressive radiological features. PVNS activates polyclonal, reactive macrophages with CSF1-receptors. Treatment options are discussed, including new possible therapies with CSF1-receptor inhibitors.
Keywords: pigmented villonodular synovitis; CSF1-receptors-inhibitors